Techno-Sociopreneur In Improving Competitiveness of Agricultural Commodities - yonaldi, sepris; Noer, Melinda; Hendri Yeni, Yulia; Nofialdi (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2023)
This paper contributes to providing an understanding of the dynamics of Techno-sociopreneur in increasing the competitiveness of agricultural commodities. First, this paper will explain the concept of Techno-sociopreneur in agricultural development from the beginning of the concept used in a scientific context. Then it will also be explained what are the components forming Techno-sociopreneur development in increasing the competitiveness of agricultural commodities, and what variables will be the novelty of research in Techno-sociopreneur research in increasing the competitiveness of agricultural commodities. The research method used is a qualitative approach with a literature review system from various best journal sources on Google Scholar, Garba Digital Reference (Garuda), Scinence direct and other relevant sources. The conclusion of this article is to explain the development of the concept of Techno-sociopreneur agricultural development can be categorized into scientific concepts of study, namely a) Innovation, b) Support of Stake Holders, c) Social, Cultural and Economic environment, and d) Empowerment. Research questions for the future related to Techno-sociopreneur based on local economic institutions in increasing the competitiveness of agricultural commodities which point to the context of the impact of Techno-sociopreneur in agricultural development, the role of Techno-sociopreneur based on local economic institutions in increasing the competitiveness of agricultural commodities and Techno-sociopreneur factor based on local economic institutions in increasing commodity competitiveness horticultural agriculture. Because studies on this have not been carried out by previous researchers both in developed countries and in developing countries.